INTRODUKSI IPTEKS PADA PETERNAKAN SAPI DI KELOMPOK TANI RAWANG SAIYO DAN KELOMPOK TANI TUAH SEPAKAT - Simel Sowmen; Khasrad Khasrad; Rusdimansyah Rusdimansyah (Jurnal Hilirisasi IPTEKS, 2018)
The activities of devotion for farmers group Rawang Saiyo and farmer groups Tuah Sepakat in Solok Regency and South Solok Regency of West Sumatra with objective to cultivate a farm beef cattle and utilisation the land for pastura; trying to overcome the problem of inadequate enclosure conditions, lack of water stock due to leaking water reservoirs and distant water sources, the length of the sewage treatment process due to inadequate processing of sewage, lack of forage that occurs during dry season. This program is carried out with counseling methods, focused discussions, piloting and training. Science and technology implementation method is carried out by applying a number of technologies according to existing problems, namely cage repair, repair of sewage treatment plants and water reservoirs and increased production of natural pastures with the introduction of cover crop legumes, water procurement efforts to farmer groups so as to ensure the sustainable of cattle farming. Utilisation of rice straw which is a by product of rice fields that are near farmer groups through straw ammonia technology so that it can be used as an alternative to forage.